The Impact of Using Audio-Visual Interactive Media in Learning Mathematics - Setiawati, Linda Mardiani; Mahsup; Abdillah; Syaharuddin (Indonesian Journal of Educational Research and Review, 2024)
In the process of learning mathematics, there are various problems, including student background, learning interest, motivation, and attitude. Based on this, this study aims to examine the effect of using audio-visual interactive media on understanding the concept of mathematics learning. The type of research used is Meta-analysis research. The research subjects are at the elementary, junior high, and high school levels. The data source is the results of previous research relevant to the research topic that meets the criteria of inclusion and exclusion. From Google Scholar, DOAJ, and Scopus indexers. The research flow are determining the research topic; developing and validating the review protocol; searching for literature; analysis; drawing conclusions; and the last stage of reporting the results. The search results found 47 eligible data with the number of students (N), F-count value, t-count value, and r-count value. The data were analyzed using JASP software by inputting the Effect Size (ES) and Standard Error (SE) values. The results of the analysis of the moderator variable test of audio-visual media-based learning for students with a P-regression value of -1.041 are greater than 0.298, meaning that the Ha Accepted hypothesis and the summary effect value are 70% with a high category. There are also the results of data analysis obtained from JASP software simulations showing a significant effect on mathematics learning media, one of which is based on Adobe Flash media at the high school level based on the results of the summary effect of 85% with a high category.